Role of tomato plant-derived food sources on Dolichogenidea gelechiidivoris, parasitic wasp of Tuta absoluta - Angeliki Syropoulou; Joel González-Cabrera; Judit Arnó; Pablo Urbaneja-Bernat (Biological Control)
Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) poses a significant threat to tomato crops worldwide. Following its detection in the Mediterranean basin, considerable efforts have been made to develop biological control programs against this pest. The larval parasitoid Dolichogenidea gelechiidivoris Marsh (Hymenoptera: Braconidae) is widely distributed in northeastern Spain and has shown promise as a natural enemy in this region. Recent studies have demonstrated that access to floral nectar can improve the biological parameters of this parasitic wasp. However, the effects of other plant-derived food sources available in tomato crops, such as plant guttation and honeydew, have yet to be explored. This study assessed the impact of plant guttation and the honeydew of two phloem-feeding insects, Myzus persicae (Sulzer) (Hemiptera: Aphididae) and Bemisia tabaci (Gennadius) (Hemiptera: Aleurodidae), on the fitness (longevity and fecundity) and performance (parasitism and sex ratio) of D. gelechiidivoris under controlled laboratory conditions. Our results demonstrated that both honeydews enhanced the fitness and performance of this parasitoid, while tomato plant guttation did not have an effect on its fitness and negatively impacted parasitism. These findings highlight honeydew as a potential food source in integrated pest management (IPM) strategies. Further research is recommended to explore the specific chemical composition of tomato plant guttation and its broader effects on beneficial insects in tomato systems.